CIRCULAR ECONOMY AND ENVIRONMENTAL BEHAVIOUR: A SYSTEMATIC LITERATURE REVIEW - Sánchez-Cubo, Francisco; Vargas-Vargas, Manuel; Mondéjar-Jiménez, José; Lasso-Dela-Vega, Elena (Copernican Journal of Finance & Accounting, 2022)
The circular economy is a top priority issue on the European green agenda. However, despite this topic having been studied for decades, there seem to be no clear ideas about how to carry out the strategies and actions that allow achieving the presupposed objectives. For this reason, this paper aims to offer a systematic literature review that might provide researchers with a synthesis paper on what has been studied so far. To achieve that, descriptive and bibliometric analyses were performed on the bibliographic data obtained from the Web of Science. That, together with the study of the most prominent extant pieces of work in the field, both historical and present, allow offering a comprehensive picture of the state of arts. Thus, the main conclusions are that there is no clear study trend and, consequently, efforts are dissipating. In addition, the problem of the budget limitation is acknowledged since it might prevent researchers from carrying out solid experiments that may allow finding general solutions to the problems derived from the implementation of circular economy strategies or actions.